Melioidosis manifesting as chronic femoral osteomyelitis in patient from Ghana - Mabayoje, DA; Kenna, DTD; Dance, DAB; NicFhogartaigh, C (Centers for Disease Control and Prevention, 2021)
A 33-year-old man from Ghana who had diabetes also had chronic osteomyelitis of the femoral shaft. Tissue samples from surgical debridement grew Burkholderia pseudomallei. He received meropenem, followed by oral trimethoprim/sulfamethoxazole and doxycycline, and fully recovered without complications. Our case report extends the range of countries in Africa as sources of culture-confirmed melioidosis.